Added Value of Cross-Border Cooperation (CBC) for the Georgia-Azerbaijan Border Regions - Dvalishvili, Tinatini (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2020)
The European context of cooperation across borders demonstrates how it engages all stakeholders from a variety of territorial levels in an intensive, collaborative dialog. This approach makes bordering regions more resilient to current and predictable threats, and is largely focused on the practical problem-solving of local needs. Regardless of the (non)material benefits the European cross-border perspective provides, the situation remains very different in the Azerbaijan-Georgia cross-border reality, where the traditional understanding of borders continues to prevail. A field inquiry has shown that territorial local communities have not had a homogenous attitude towards the borderline and their neighbors, and that local municipalities lack the power and credibility to deal with local challenges autonomously. Unlike the European CBC, this cross-border context does not include the elements of bottom-up cross-border planning and locally institutionalized forms of collaboration.

Europejski kontekst współpracy transgranicznej pokazuje, że angażuje ona wszystkich interesariuszy z różnych poziomów terytorialnych w intensywny dialog oparty na współpracy. Podejście to sprawia, że sąsiadujące regiony są bardziej odporne zarówno na istniejące, jak i przewidywalne zagrożenia i jest w dużej mierze skoncentrowane na praktycznym rozwiązywaniu problemów związanych z potrzebami lokalnymi. Niezależnie od (nie)materialnych korzyści, jakie zapewnia europejska perspektywa transgraniczna, rzeczywistość transgraniczna Azerbejdżanu i Gruzji, gdzie nadal dominuje tradycyjne rozumienie granic, jest bardzo odmienna. Badanie terenowe wykazało, że lokalne społeczności terytorialne nie mają jednolitego stosunku do pogranicza i swoich sąsiadów, a samorządom brakuje władzy i wiarygodności, aby samodzielnie radzić sobie z lokalnymi wyzwaniami. W przeciwieństwie do europejskiej współpracy transgranicznej, ten kontekst nie obejmuje elementów oddolnego planowania transgranicznego i lokalnie zinstytucjonalizowanych form współpracy.
Wartość dodana współpracy transgranicznej dla regionów przygranicznych Gruzji i Azerbejdżanu
Keywords: cross-border cooperation (CBC); added value; functional cross-border regions (CBRs); Georgia-Azerbaijan borderline; współpraca transgraniczna; wartość dodana; funkcjonalne regiony transgraniczne; pogranicze Gruzji i Azerbejdżanu